Montaigne e Descartes: do Que Sais-Je? ao Je Pense, Donc Je Suis - Azizi, Diego dos Anjos (2014)
This paper sets forth a criticism of a certain interpretation of the influence of Michel de Montaigne s skepticism on the philosophy of René Descartes. This interpretation is upheld by Alexandre Koyré and Etienne Gilson, and leads to the conclusion that Montaigne, while searching for a kind of certainty about himself in the Writings and abandoning his search for certainty in the world, ultimately encounters nothing other than doubt. Descartes would be the overcoming of Montaigne s failure, with Discourse on the Method being a victorious text. Nonetheless, we shall demonstrate that Montaigne did not fail in his Essays, nor was his supposed skepticism responsible for having an overwhelming influence on Cartesian philosophy